Long-Term Safety of Transplanting Human Bone Marrow Stromal Cells into the Extravascular Spaces of the Choroid of Rabbits - Adi Tzameret; Sapir E. Kalish; Ifat Sher; Lea Twito; Amilia Meir; Itay Levy; Shlomo Margel; Iris Moroz; Mordechai Rosner; Avraham J. Treves; Arnon Nagler; Michael Belkin; et al. (Stem Cells International)
Incurable neuroretinal degeneration diseases cause severe vision loss and blindness in millions of patients worldwide. In previous studies, we demonstrated that transplanting human bone marrow stromal cells (hBMSCs) in the extravascular spaces of the choroid (EVSC) of the Royal College of Surgeon rats ameliorated retinal degeneration for up to 5 months. Assessing the safety of hBMSC treatment and graft survival in a large animal is a crucial step before initiating clinical trials. Here, we transplanted hBMSCs into the EVSC compartment of New Zealand White rabbits. No immunosuppressants were used. Transplanted cells were spread across the EVSC covering over 80 percent of the subretinal surface. No cells were detected in the sclera. Cells were retained in the EVSC compartment 10 weeks following transplantation. Spectral domain optical coherence tomography (SD-OCT) and histopathology analysis demonstrated no choroidal hemorrhages, retinal detachment, inflammation, or any untoward pathological reactions in any of transplanted eyes or in the control noninjected contralateral eyes. No reduction in retinal function was recorded by electroretinogram up to 10 weeks following transplantation. This study demonstrates the feasibility and safety of transplanting hBMSCs in the EVSC compartment in a large eye model of rabbits.